Identification and molecular weight characterization of antigens from Candida albicans that are recognized by human sera. - Strockbine, N A (1984)
Antigenic components in the cytoplasmic extract of Candida albicans were examined after fractionation by concanavalin A-Sepharose and DEAE-Sephacel ion-exchange chromatography. Fractions from the DEAE column were tested by fused rocket immunoelectrophoresis for their reactivity with antibodies in the sera of 20 patients with disseminated candidiasis. Three groups of fractions (regions A, B, and C) from the DEAE column were defined by their reactivity with these sera. Immunoblot analysis with 20 human sera identified 18 antigenic components in regions A, B, and C. Region A contained nine antigens, region B contained four antigens, and region C contained five antigens. Region A contained an antigen with an apparent molecular weight of 48,000 that was recognized by 7 of 10 sera from patients with disseminated candidiasis. Immunoprecipitation experiments with labeled proteins from region A and 51 human sera also demonstrated the presence of a major antigen whose apparent molecular weight is 48,000 to 52,000. The 48- to 52-kilodalton protein is an abundant protein in region A and is the most frequently recognized protein by antibodies in the sera of patients with disseminated candidiasis. Patients with disseminated candidiasis had significantly higher levels of antibody (immunoglobulin G) (P less than 0.001) directed against the 48- to 52-kilodalton protein than did patients with noninvasive forms of candidiasis, patients with other fungal infections, or normal, healthy persons.